2019
DOI: 10.1111/petr.13364
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive differentiation of non‐rejection kidney injury from acute rejection in pediatric renal transplant recipients

Abstract: Acute kidney injury (AKI) is a major concern in pediatric kidney transplant recipients, where non‐alloimmune causes must be distinguished from rejection. We sought to identify a urinary metabolite signature associated with non‐rejection kidney injury (NRKI) in pediatric kidney transplant recipients. Urine samples (n = 396) from 60 pediatric transplant participants were obtained at time of kidney biopsy and quantitatively assayed for 133 metabolites by mass spectrometry. Metabolite profiles were analyzed via pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In a single-center pediatric cohort study [ 64 ], Archdekin et al extended their previous work for detection of patterns related to allograft kidney injuries using the same set of quantified metabolites for identification of clinically relevant classifier of NRKI independent of acute rejection. Urine samples without rejection were split into NRKI, pre-NRKI, and no NRKI.…”
Section: Metabolomics In Kidney Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a single-center pediatric cohort study [ 64 ], Archdekin et al extended their previous work for detection of patterns related to allograft kidney injuries using the same set of quantified metabolites for identification of clinically relevant classifier of NRKI independent of acute rejection. Urine samples without rejection were split into NRKI, pre-NRKI, and no NRKI.…”
Section: Metabolomics In Kidney Transplantationmentioning
confidence: 99%
“…The NRKI discriminant score distinguished between NRKI from samples with no NRKI and pre-NRKI. In addition, the NRKI score sensitivity was found to significantly discriminate between NRKI and rejection (CMR, AMR, and mixed rejection): in the subset of all samples with elevated serum creatinine, the score was successfully tested for differentiating the two different conditions [ 64 ]. Regarding the NRKI score, some metabolites (such as Proline [ 65 ] or ADMA [ 65 , 66 ]) have been previously linked to reduced GFR [ 19 ].…”
Section: Metabolomics In Kidney Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size determined for this study aligns with previously published drug metabolomic studies and cisplatin AKI incidence. [69][70][71][72][73] Metabolomics analysis. Metabolomics analyses of serum and urine for the discovery cohort will be done using a Waters Xevo G2-S quadrupole time-of-flight (QToF) mass spectrometer.…”
Section: Sample Size Considerationsmentioning
confidence: 99%
“…Characteristic urine NMR spectra were also demonstrated in murine renal ischemia-reperfusion injury models [17,18]. Archdekin et al using mass spectrometry of urine samples demonstrated the potential of a urine metabolite classifier to detect non-rejection kidney injury in pediatric kidney transplant patients and non-invasively discriminated non-rejection kidney injury from rejection [19]. While metabolomic profiles have been investigated in prematurity, low birth weight neonates, perinatal asphyxia, pediatric respiratory and neurological diseases, gastrointestinal diseases and inborn errors of metabolism, only very few clinical studies have been published that investigated the application of a metabolomic approach in pediatric AKI [20,21].…”
Section: Introductionmentioning
confidence: 99%